Childhood cancer in Gondar University Hospital, Northwest Ethiopia - Yifru, Sisay (BMC Res Notes, 2015)
BACKGROUND: Childhood cancer becomes a public health problem in developing countries which aggravates the burden of childhood mortality by infectious diseases and malnutrition. In poor countries, the death rate for most pediatric cancers is almost 100 %. This study attempts to determine the magnitude, patterns and trends of pediatric malignancies in the study area which is important in re-evaluating existing services and in improving facilities and patient care. METHODS: A retrospective study of 3 year period were carried out among all children aged below 15 years old admitted into the pediatric wards of Gondar University Hospital, Northwest Ethiopia. The charts of all children aged below 15 years old admitted in the pediatric wards due to cancer were reviewed by using the data collection format. Data were entered and analyzed using SPSS version 20 statistical package. RESULT: A total of 71 cancer cases were diagnosed and admitted to the pediatrics ward during the study period. More than two-third of the study subjects 50 (70.4 %) were males. The mean age of study subjects was 7 ± 4 year where majority 26 (36.6 %) of the study subjects were ≥10 years. Of all, 43 (60.6 %) were hematological malignancy followed by Wilms tumor 13 (18.3 %), Neuroblastoma 5 (7 %), Rhabdomyosarcoma 3 (4.2 %), Brain tumor 3 (4.2 %), Hepatoblastoma 2 (2.8 %). More than two-third of cases were found to be concomitantly malnourished being stunted, wasted and under weight. Nearly half of patients had not received chemotherapy and majority of those started chemotherapy did not complete all the treatment cycles. Shortage and absence of safe and affordable chemotherapy drugs were the major reasons for therapy interruption. CONCLUSION: The study shows increasing childhood cancer cases over the years. Hematological malignancy takes the leading prevalence followed by Wilms tumor and Neuroblastoma. The majority of cases were also discharged without any clinical change that had the only death option. Therefore, the government and the hospital should give emphasis to establish cancer therapy centers and insure accessibility and affordability of chemotherapy drugs.